1998
DOI: 10.1080/08897079809511379
|View full text |Cite
|
Sign up to set email alerts
|

Differences in perimenstrual symptoms between cocaine‐abusing and non‐cocaine‐abusing women

Abstract: Cocaine abuse among women has become a major health problem in the United States, yet there is little information in the literature concerning the effects of this form of substance abuse on a woman's reproductive system. This study of 65 women in residential treatment for cocaine abuse and 65 non-cocaine-abusing women was undertaken to determine if there are differences in frequency or severity of perimenstrual symptoms between these two groups of women. Data were collected by questionnaire and included demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One found that nonprescription drug use increased (Marks et al, 1994). Another study found that cocaine abusers reported more frequent and more severe PMS-like symptoms than nonabusers (Littleton, 1998). The latter finding could indicate some effect of cocaine abuse aggravating PMS, but it could also indicate that PMS-like symptoms predispose individuals toward cocaine abuse.…”
Section: Evidence For Changes In Self-control During the Luteal Phasementioning
confidence: 99%
“…One found that nonprescription drug use increased (Marks et al, 1994). Another study found that cocaine abusers reported more frequent and more severe PMS-like symptoms than nonabusers (Littleton, 1998). The latter finding could indicate some effect of cocaine abuse aggravating PMS, but it could also indicate that PMS-like symptoms predispose individuals toward cocaine abuse.…”
Section: Evidence For Changes In Self-control During the Luteal Phasementioning
confidence: 99%